How to read Donald Duck : imperialist ideology in the Disney comic - Dorfman, Ariel; Mattelart, Armand (Pluto Press, 2019)
Censored and condemned, this is a highly controversial Marxist critique of how our favourite cartoons are vehicles for capitalist ideology.